Development Of Rice-Based Snacks Fortified With Pumpkin Flour - Othman, Nur Hanani (Pusat Pengajian Teknologi Industri, 2021)
This study was carried out to investigate the effects of three levels of pumpkin flour on the nutritional composition, physical properties (expansion ratio, bulk density, and colour) and textural properties of the rice-based snacks fortified with pumpkin flour. Extruded snacks were produced by substituting black rice with different percentage of pumpkin flour (5, 10 and 15%). Extruded snack made with 50% black rice and 50% broken rice (fix) was used as a control. Proximate analysis was conducted to determine the nutritional composition of the extrudates with different formulation.